Cartesian decomposition of C-normal operators. Issue 21 (20th December 2022) - Ramesh, G.; Sudip Ranjan, B.; Venku Naidu, D.
Abstract : In this note, we establish the cartesian decomposition of C -normal operator on a complex separable Hilbert space. Using this we give two characterizations of C -normal operators. These characterizations are useful in checking C -normality of an operator. We illustrate these results with examples.